Lung cancer diagnosed following an emergency admission: mixed methods study of the management, outcomes and needs and experiences of patients and carers - Wilcock, Andrew; Crosby, Vincent; Hussain, Asmah; McKeever, Tricia M.; Manderson, Cathann; Farnan, Sarah; Freer, Sarah; Freemantle, Alison; Littlewood, Fran; Caswell, Glenys; Seymour, Jane (Elsevier, 2016)
Background